2016
DOI: 10.21273/jashs03870-16
|View full text |Cite
|
Sign up to set email alerts
|

Simple Sequence Repeat Markers Reveal Genetic Diversity Within and among Landrace Collections of Citron and Dessert Watermelon from South Africa

Abstract: Genetic diversity analysis is fundamental for effective breeding and genetic conservation. The objective of this study was to determine the genetic diversity present among dessert watermelon (Citrullus lanatus var. lanatus) and citron watermelon (C. lanatus var. citroides) landraces widely grown in South Africa and to select genetically diverse and complimentary genotypes for strategic breeding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…The citron watermelon root architecture has a primary taproot and several lateral roots [6]. Genetic variability has been reported in the species for morphological traits including RSA traits [17][18][19][20][21][22][23][24][25]. Using a genetically diverse population of citron watermelon accessions collected and grown in the drier parts of South Africa by small-holder farmers, Mandizvo, et al [26] observed variability in estimated root percentage, taproot length and root dry mass among the accessions after exposure to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The citron watermelon root architecture has a primary taproot and several lateral roots [6]. Genetic variability has been reported in the species for morphological traits including RSA traits [17][18][19][20][21][22][23][24][25]. Using a genetically diverse population of citron watermelon accessions collected and grown in the drier parts of South Africa by small-holder farmers, Mandizvo, et al [26] observed variability in estimated root percentage, taproot length and root dry mass among the accessions after exposure to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The non‐sweet citron watermelon types with yellow and orange‐flesh are favoured for cooking various traditional dishes in SSA (Mashilo et al, 2016; Nantoumé et al, 2012, 2013; Ngwepe et al, 2019, 2021). Orange‐fleshed sweet dessert watermelon ( C. lanatus var.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the nutritional, socio‐economic importance and breeding value of citron watermelon, the crop is underutilized and its economic value is not fully realized and exploited for food, medicine and commercial applications in SSA (Mashilo et al, 2016, 2017; Ngwepe et al, 2019). As a result, there are no improved varieties released and commercialized for production, processing or value adding (Ngwepe et al, 2021; Nkoana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations